Synthesis of purines and adenines containing the hexafluoroisopropyl group - Petrov, Viacheslav; Dooley, Rebecca J.; Marchione, Alexander A.; Diaz, Elizabeth L.; Clem, Brittany S.; Marshall, William (Beilstein Journal of Organic Chemistry, 2020)
Several new derivatives of adenine, purine, and theophylline containing the (CF3)2CH group connected to a nitrogen atom of the imidazole ring were prepared by the reaction of 2,2,4,4-tetrakis(trifluoromethyl)-1,3-dithietane (1) with the corresponding substrates, resulting in the selective alkylation of one of the nitrogen atoms of the imidazole ring. The reaction proceeds under mild conditions in a polar solvent, giving the alkylated products in 47–78% yield. While for purine and 4- and 5-azabenzimidazole, the reaction led to a mixture of two isomers, the reaction of adenine and the corresponding 2-fluoro derivative was regioselective, resulting in the formation of only one isomer in each case. The alkylation of theophylline led to the formation of a new derivative of caffeine.
Keywords: adenine; caffeine; cyclic dimer of hexafluorothioacetone; hexafluoroisopropyl group; purine; 2,2,4,4-tetrakis(trifluoromethyl)-1,3-dithietane; theophylline